Examen Especial al Departamento de Talento Humano de la COAC Indígena SAC Ltda. Matriz Ambato, periodo 2022 - Tubon Asas, Juan Gabriel (2024)
ABSTRACT: This research, titled "SPECIAL EXAM TO THE DEPARTMENT OF HUMAN TALENT OF THE COAC INDIGENA SAC LTDA. MATRIZ AMBATO, PERIOD 2022," evaluates the selection, hiring, and retention process of personnel in accordance with current labor regulations. The research was conducted using a qualitative approach, analyzing the information provided by the cooperative. The primary findings of the examination revealed significant deficiencies in the entity's operations. These included inadequate planning for staff training, lack of updates in the functions and hiring manuals, and errors in the digitalization of contract preparation processes. These shortcomings pose a risk to the department's regulatory compliance and efficiency. Therefore, it was recommended that human talent management processes be improved with current regulations, a continuous training plan for staff development and execution, functions and hiring manuals be reviewed and updated, and quality control carried out. In this way, contract preparation processes help improve contracting processes by current labor regulations and thus reduce the risks associated with identified results. Keywords: Special Examination, Hiring, Labor Regulations, Human Talent.